Mapping The Transformation of Economic Structure in Solo Raya in 2014-2023: Geospatial Approach - Habib Bahtiar; Evi Gravitiani; Mulyanto Mulyanto; Sarjiyanto Sarjiyanto; Wang Yao Hong (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2024)
Indonesia has a variety of geographical landscapes that can affect the economic structure in each of its regions. This study aims to understand changes in the contribution and growth of economic sectors in the Solo Raya region, as well as to identify spatial patterns in economic transformation in 2014-2023. The method used is quantitative descriptive with a geospatial approach, using Location Quotient (LQ) and Dynamic Location Quotient (DLQ) analysis tools, Growth Ratio Model (MRP), and overlay analysis mapped with software Tableau. The results showed that the economic structure of Solo Raya was transformed from 2014 to 2023. Some districts, such as Boyolali, changed from category 1 to category 2 in the MRP analysis, while other districts, such as Sukoharjo and Sragen, underwent the opposite transformation. Overall, in the LQ and DLQ analysis, the processing industry sector and the financial services sector have great potential to be developed to support economic growth in the Solo Raya area. In addition, the overlay results show that some districts still make significant contributions but have small growth, while other districts do not experience significant changes in their economic structure.